Short-circuit protection for MV & LVDC grid - Lee, Kok Cheung (2015)
A DC medium voltage (MV) and low voltage (LV) power distribution network will be proposed and the protection aspects will be discussed in this paper. This paper is mainly focused on the short-circuit overcurrent protection system of the future MV/LVDC distribution network. The proposed MV/LVDC distribution network would be modeled using PSCAD. Positive phase to ground faults normally observed in the unipolar network will be simulated and analyzed. Typical response times to clear the different types of short-circuit fault would be estimated. The response time will be compared with proposed tripping time.